The white man's burden : why the West's efforts to aid the rest have done so much ill and so little good - Easterly, William, 1957- (New York : Penguin Press, 2006)
"The White Man's Burden is about what William Easterly calls the twin tragedies of global poverty. The first is that so many are seemingly fated to live horribly stunted, miserable lives and die such early deaths. The second is that after fifty years and more than $2.3 trillion in aid from the West addressing the first tragedy, there is so shockingly little to show for it. We'll never solve the first tragedy, William Easterly argues, unless we figure out the second." "So what's going on? The ironies are many: We preach a gospel of freedom and individual accountability, yet we intrude on the inner workings of so-called developing countries through bloated aid bureaucracies like the IMF and World Bank that are accountable to no one for the effects of their prescriptions. We've cheered our victory over communism, but seven decades after Stalin's five-year plans, we're still imposing five-year plans of our own on the wretched of the earth. We take all the credit for the economic success stories of the last fifty years, like South Korea and Taiwan, when in fact we deserve very little of it. We deny all accountability for the fact that despite more than half a trillion dollars poured into Africa and other regions, and one "big new idea" after another, the majority of places in which we've meddled the most are in fact no better off or are even worse off than they were before. Could there be a connection? Could it be that we don't know as much as we think we do about the magic spells that will open the door to the road to wealth?" "Absolutely, William Easterly thunders in this sometimes angry, sometimes irreverent, but always clear-eyed and rigorous book. He argues that we need to face our own history of ineptitude and draw the proper conclusions, especially at a time when the question of our ability to transplant Western institutions onto foreign soil so that they take root has become one of the most pressing issues we face."--BOOK JACKET.
Ch. 1. Planners versus searchers -- Pt. I. Why planners cannot bring prosperity -- Ch. 2. The legend of the big push -- Ch. 3. You can't plan a market -- Ch. 4. Planners and gangsters -- Pt. II. Acting out the burden -- Ch. 5. The rich have markets, the poor have bureaucrats -- Ch. 6. Bailing out the poor -- Ch. 7. The healers : triumph and tragedy -- Pt. III. The white man's army -- Ch. 8. From colonialism to postmodern imperialism -- Ch. 9. Invading the poor -- Pt. IV. The future -- Ch. 10. Homegrown development -- Ch. 11. The future of western assistance.
Includes bibliographical references and index.
Keywords: Economic assistance -- Developing countries; Poverty -- Prevention